EFEKTIVITAS PENERAPAN SISTEM PENGENDALIAN INTERNAL PEMBERIAN KREDIT PADA PD BKK GONDANGREJO KARANGANYAR - Erlina Sih Rahayu & Mulyono (Universitas Slamet Riyadi, 2018)
This study aims to determine effectiveness of the implementation of internal control system in provision credit in PD BKK Gondangrejo Karanganyar. The research method using qualitative research with descriptive analysis technique. Methods of data collection using questionnaires, documentation, observation, and interviews. Results of this research showed that credit provision system adopted by PD BKK Gondangrejo Karanganyar has been implemented in accordance with the provisions on the procedure of crediting starting from credit applications, investigation and credit analysis, approval of loan application, disbursement, until payment. Credit system supported by the implementation of an effective internal control system, which has met the five elements of the internal control system, namely the control environment, risk interpretation, control activities, information and communication, and monitoring. Conclusion, credit provision procedures and internal control system of credit provision adopted by PD BKK Karanganyar is clear and very good. However, PD BKK Gondangrejo Karanganyar should establish a special mechanism for identifying and tracking inconsistencies with customers or borrowers as well as other outside parties in terms of operational, financial and compliance with prevailing policies.Keywords: internal control system, lending